Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1159/000068622
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenesis: Current Clinical Data and Future Perspectives

Abstract: Neovascularization is a prerequisite for progressive growth of solid tumors and their metastases. This process is tightly regulated by a large number of proangiogenic and antiangiogenic factors such as VEGF, bFGF and matrix-metalloproteinases. The inhibition of angiogenesis is an innovative therapeutic approach and could represent a powerful adjunct to traditional therapy of malignant tumors. Preclinical trials have been very successful but in clinical studies meaningful response rates could only be shown in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…[6][7][8] Here, these anti-angiogenic inhibitors are collectively reviewed and their anti-angiogenic effect and subsequent anti-tumor effect estimated. Then, a novel cancer chemotherapy targeting the angiogenic vasculature, anti-neovascular therapy (ANET), is discussed which uses traditional anti-cancer agents or photosensitizer.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Here, these anti-angiogenic inhibitors are collectively reviewed and their anti-angiogenic effect and subsequent anti-tumor effect estimated. Then, a novel cancer chemotherapy targeting the angiogenic vasculature, anti-neovascular therapy (ANET), is discussed which uses traditional anti-cancer agents or photosensitizer.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Compared with protein therapy, there are several potential advantages. As a prelude to the potential clinical application of RI gene therapy, we cloned the human ri gene and inserted it in a retroviral vector pLNCX.…”
mentioning
confidence: 99%
“…To date, no clear correlation has emerged between circulating and receptor bound levels of VEGF and other angiogenic factors. A large number of studies have demonstrated a strong association between elevated expression of VEGF by primary tumors and advanced disease or poor prognosis (including lymph node metastasis) in a variety of cancers [18,[29][30][31]. Protein and mRNA have been measured in tumor samples, and protein has also been measured in the circulation.…”
Section: Angiogenic Growth Factors and Their Receptorsmentioning
confidence: 99%